Analisis Peninggalan Keagamaan Hindu-Buddha di Kedatuan Sriwijaya: Perspektif Sosio-Kultural - Susanti, LR Retno; Fatihah, Husnul; Mariyani, Mariyani; Hidayanti, Mailiza; Oktarina, Tia (Universitas Hamzanwadi, 2024)
This research aims to discover how the existence and development of the Hindu-Buddhist religion in Kedatuan Sriwijaya influenced society's social structure, culture and values at that time. The methods used in this research are literature study, field data collection, archaeological analysis, and interviews with historical and cultural experts. Religious life in the Srivijaya Kingdom, founded around the 7th to 14th centuries AD, was dominated by Hinduism and Buddhism. In that period, these two religions played an important role in shaping the culture, society, and politics of Sriwijaya. Socio-cultural, the start of the Cultural Integration of Hindu-Buddhist Heritage, reflects the solid cultural integration between these religions and local culture in Kedatuan Sriwijaya. Religious Harmony: this relic shows the existence of harmony between followers of these religions in Sriwijaya society. Religious Expansion: in this section, the Srivijaya chiefdom was essential in spreading Buddhism in Southeast Asia. Education Center Monks and Brahmins who visited Sriwijaya brought religious and cultural knowledge and influenced religious education. Economy and Trade started with Sriwijaya's strategy of developing the trade sector by building a substantial fleet of ships and controlling robust trading ports. Then, the artistic heritage, Hindu-Buddhist artistic and architectural heritage in Sriwijaya reflects the influence of the culture and religious beliefs that inspired it.